Future Targets for Female Sexual Dysfunction. Issue 8 (1st August 2016) - Farmer, Melissa; Yoon, Hana; Goldstein, Irwin
ABSTRACT: Introduction: Female sexual function reflects a dynamic interplay of central and peripheral nervous, vascular, and endocrine systems. The primary challenge in the development of novel treatments for female sexual dysfunction is the identification and targeted modulation of excitatory sexual circuits using pharmacologic treatments that facilitate the synthesis, release, and/or receptor binding of neurochemicals, peptides, and hormones that promote female sexual function. Aim: To develop an evidence-based state-of-the-art consensus report that critically integrates current knowledge of the therapeutic potential for known molecular and cellular targets to facilitate the physiologic processes underlying female sexual function. Methods: State-of-the-art review representing the opinions of international experts developed in a consensus process during a 1-year period. Main Outcome Measures: Expert opinion was established by grading the evidence-based medical literature, intensive internal committee discussion, public presentation, and debate. Results: Scientific investigation is urgently needed to expand knowledge and foster development of future treatments that maintain genital tissue integrity, enhance genital physiologic responsiveness, and optimize positive subjective appraisal of internal and external sexual cues. This article critically condenses the current knowledge of therapeutic manipulation of molecular and cellular targets within biological systems responsible for female sexual physiologic function. Conclusion: Future treatment targets include pharmacologic modulation of emotional learning circuits, restoration of normal tactile sensation, growth factor therapy, gene therapy, stem cell–based therapies, and regenerative medicine. Concurrent use of centrally and peripherally acting therapies could optimize treatment response.